Free radical properties of metal complexes - Szentmihályi Klára; Blázovics Anna; Vinkler Péter; Free Radical Research, 2002, Szeged (2003)
Since metals are cable of catalysing the free radical reactions, different metal (Mg, Mn, Zn) compounds were studied to determine their hydroxyl radical generating and/or scavenging abilities depending on ligand in a H2O2/•OH -luminol system with or without microperoxidase. Magnesium oxide, magnesium gluconate and manganese gluconate increase the free radical reactions in the H2O2/•OH -luminol system. Most of examined metal compounds have different hydroxyl radical scavenging activity in H2O2/•OH- microperoxidase -luminol system. Magnesium citrate has the highest antioxidant effect, while manganese compounds seem to be prooxidant. Vitamin E and C elevate the free radical level in this experimental system.